2011
DOI: 10.1063/1.3521268
|View full text |Cite|
|
Sign up to set email alerts
|

Density, structure, and dynamics of water: The effect of van der Waals interactions

Abstract: It is known that ab initio molecular dynamics (AIMD) simulations of liquid water at ambient conditions, based on the generalized gradient approximation (GGA) to density functional theory (DFT), with commonly used functionals fail to produce structural and diffusive properties in reasonable agreement with experiment. This is true for canonical, constant temperature simulations where the density of the liquid is fixed to the experimental density. The equilibrium density, at ambient conditions, of DFT water has r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
208
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(251 citation statements)
references
References 69 publications
38
208
5
Order By: Relevance
“…The plane--wave cutoff energy remained at 810 eV. As recent work has shown that the 650 description of water in DFT calculations is improved by the inclusion of corrections for the long--range 651 dispersion (Wang et al, 2011), the calculations of the SeO 3 2--incorporation at the calcite--water interface 652 were additionally studied with the PBE+D--USP method, where dispersion corrections are included 653 according to the method of Tkatchenko and Scheffler (2009). As our previous calculations revealed 654 periodicity in the structure of the water layer, the water--interface incorporation was modeled using 655 PBE+D for the two distinct sites, Se1 and Se2.…”
Section: Usp and Pbe+d--usp) 643mentioning
confidence: 99%
“…The plane--wave cutoff energy remained at 810 eV. As recent work has shown that the 650 description of water in DFT calculations is improved by the inclusion of corrections for the long--range 651 dispersion (Wang et al, 2011), the calculations of the SeO 3 2--incorporation at the calcite--water interface 652 were additionally studied with the PBE+D--USP method, where dispersion corrections are included 653 according to the method of Tkatchenko and Scheffler (2009). As our previous calculations revealed 654 periodicity in the structure of the water layer, the water--interface incorporation was modeled using 655 PBE+D for the two distinct sites, Se1 and Se2.…”
Section: Usp and Pbe+d--usp) 643mentioning
confidence: 99%
“…35 and some examples for water within the approach B can be found in Ref. 36,37 . Notice that in approaches A and B, the energy is obtained "on the fly" for each configuration either by solving the Schrödinger equation or by performing density functional theory (DFT) calculations.…”
Section: Abcd In the Modelling Of Watermentioning
confidence: 99%
“…Similarly, AI-DFT computations of water predict structural and coexistence properties that differ from those of experiment, highlighting the need for significant advances in the development of functionals that handle more accurately dispersive interactions. 46 In this paper, we employ point charge models. Given the wide range of studies performed with this approach, they provide a good starting point to address the main aim of this paper, namely, the computation of intrinsic interfacial structure, and to obtain a qualitative view of the structure of interfacial solutions for a wide range of salt conditions.…”
Section: A Model and Simulation Detailsmentioning
confidence: 99%